Pengaruh Current Ratio Dan Earning Per Share Terhadap Harga Saham Indeks Lq-45 Di Bursa Efek Indonesia - Niar, Hikma; Irmawati (STIM-LPI Makassar, 2024)
This study aims to determine the effect of current ratio and earnings per share on stock prices partially and simultaneously. The results of this study indicate that partially the current ratio has no effect on stock prices as evidenced by a coefficient of -0.214 and a t-count of -1.813 with a significance of 0.074. The coefficient of determination test results obtained an adjusted R2 value of 0.720 indicating that the stock price is influenced by the current ratio and earnings per share of 72%.